Direct Detection of Triacetone Triperoxide (TATP) in Real Banknotes from ATM Explosion by EASI‐MS. Issue 4 (11th April 2017) - Nascimento Correa, Deleon; Melendez‐Perez, Jose J.; Jardim Zacca, Jorge; Borges, Rodrigo; Morgado Schmidt, Eduardo; Eberlin, Marcos Nogueira; Meurer, Eduardo César
Abstract: In Brazil, automated teller machine (ATM) has become a major target of theft incursions toward explosion. Efficient analysis of explosives residues on suspect banknotes is a serious issue in forensic labs, and guide to the crime solution. Easy ambient sonic‐spray ionization mass spectrometry (EASI‐MS) is shown to be a simple and selective screening tool to identify peroxide explosives on real banknotes collected from ATM explosion. Analyses were carried out directly on the banknotes surfaces without any sample preparation, identifying triacetone triperoxide (TATP) and diacetone diperoxide (DADP). Homemade EASI source was coupled to ultrahigh‐resolution and ultrahigh accuracy FT‐ICR MS and revealed the ion of m / z 245 correspondent to sodiated TATP [C9 H18 O6 Na] + and the ion of m / z 171 related to sodiated DADP [C6 H12 O4 Na] +, ions that is the sodiated DADP and the ions of m / z 173 and 189 related to [C6 H14 O4 Na] + and [C6 H14 O4 K] +, respectively, which are associated to chemical markers of TATP domestic route synthesis. EASI source coupled to a single quadrupole mass spectrometer provides an intelligent and simple way to identify the explosives TATP, DADP and its domestic synthesis markers. Abstract :